2019
DOI: 10.1371/journal.pone.0225947
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic power in hurling with respect to position and halves of match-play

Abstract: The current investigation compared the metabolic power and energetic characteristics in team sports with respect to positional lines and halves of match-play. Global positioning system (GPS) technology data were collected from 22 elite competitive hurling matches over a 3-season period. A total of 250 complete match-files were recorded with players split into positional groups of full-back; half-back; midfield; half-forward; full-forward. Raw GPS data were exported into a customized spreadsheet that provided e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 34 publications
(100 reference statements)
1
30
0
1
Order By: Relevance
“…However, it was reported that P met maintains a strong and consistent relationship with the measures of internal load during low-to-high intensity locomotor activities [21]. Therefore, P met could be a satisfactory way to estimate with accuracy the training and match demands [12,22] and to classify the locomotion intensity in team sports [21,28].…”
Section: Plos Onementioning
confidence: 98%
See 1 more Smart Citation
“…However, it was reported that P met maintains a strong and consistent relationship with the measures of internal load during low-to-high intensity locomotor activities [21]. Therefore, P met could be a satisfactory way to estimate with accuracy the training and match demands [12,22] and to classify the locomotion intensity in team sports [21,28].…”
Section: Plos Onementioning
confidence: 98%
“…Moreover, P met can be sensitive to decrements in running performance during competition [ 23 25 ] and it could be used to account for positional differences [ 23 , 25 ]. Therefore, the combination of the P met approach and the traditional speed-threshold metrics should be used to provides a more comprehensive assessment of the intermittent running demands typically occurring in team sports [ 15 17 , 21 , 24 , 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data collected from the GPS units included total distance (m), HSR (17-21.9 km•h −1 ), sprint distance (≥22 km•h −1 ) [1,2] and high metabolic load distance (HMLD: a metric that combines HSR distance, and distance covered while accelerating and decelerating) [9]. The total number of sprints (≥22 km•h −1 ) were also collected [17].…”
Section: Methodsmentioning
confidence: 99%
“…Between-position running performance were recorded in hurling at U17 [23], U21 [1], and senior [8][9][10]. Results showed that running performance within positions decreased in the second half in hurling [1,2,9], similar to other team sports [24][25][26]. Currently, there are no data available that describe the total distance, HMLD, sprint distance, and the number of sprints between quarters in senior hurling.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation